Peran Ulama Perempuan dalam Menanggapi Perkawinan Anak di Indonesia - Kristianto, Paulus Eko (Sawwa: Jurnal Studi Gender, 2018)
In this article, the author tries to ask the question of the role of female scholars in responding to child marriage in Indonesia? The author tries to answer this question with the literature study method on various books and describes them in the sub-discussion of female scholars; a description of the situation of child marriage in the world and Indonesia; child marriage, law, and legal practice; and the role of female scholars in responding to child marriage. Through this step, the authors hope this article can contribute perspectives and alternatives to women scholars in responding to child marriage in Indonesia.